B-1 B cell progenitors transiently and partially express keratin 5 during differentiation in bone marrow. Issue 3 (March 2016) - Hanafusa, Takaaki; Kato, Kenichi; Azukizawa, Hiroaki; Miyazaki, Jun-ichi; Takeda, Junji; Katayama, Ichiro
Highlights: Ectopic K5 expression in lymphocytes has never been reported. We show an ectopic K5 expression in B-1 B cell by fate mapping. B-1 B cell progenitors transiently and partially expressed K5 in bone marrow. They are potent for natural antibody production and antigen presentation. Abstract: Background: Keratin 5 (K5) is a cytoskeletal tissue-specific protein expressed in the epithelial cells of skin and esophagus and ectopic K5 expression in lymphocytes has never been reported. Objective: Here we demonstrate an ectopic epidermal self-protein expression in B-1 B cell by fate mapping of K5-expressing cells. Methods: K5-Cre × CAG-CAT-loxP-EGFP double Tg (K5 × GFP) mice that express enhanced GFP under the control of the K5 promoter were employed. Results: Unexpectedly, B220 + GFP + cells were found in LN, spleen, peripheral blood and peritoneal cavity. These cells were IgM + IgD low CD23 − CD43 + CD19 + CD93 −, indicating that they were B-1 B cells. The number of B220 + GFP + cells was significantly larger in spleen than in the other tissues tested. Although GFP + B-1 cells did not express K5 in the periphery, Lin − CD93 + B220 low−neg CD19 + B-1 B cell progenitors expressed GFP and B220 + CD93 + progenitor cells expressed K5 and MHC-class II in BM, indicating that GFP + B-1 cells transiently expressed K5 and the progenitor cells were potential APC. GFP + B-1 cells in the periphery continued expressing MHC class II and had exogenous antigen-presenting capacity comparable to non-follicular B cells. GFP + B-1 cells spontaneously secreted more IgM than GFP − B-1 cells in vitro. Conclusion: These results indicate that B-1 B cells transiently and partially express K5 in BM and are potent for both natural antibody production and antigen presentation.